(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Electronic Government defined as «The employment of the Internet and the world-wide web for delivering government information and services to the citizens. One important function of electronic government is to reduce the risk of corruption. E-government creates «transparent communication» that allows citizens to apply directly through the internet to the government, removes officials as mediators between citizens and the government, thus reducing risk of administrative corruption. The article proposes to consider the opportunities for reducing the petty corruption in Kazakhstan due to introduction of electronic services Key words: electronic government, transparency, administrative barriers, bureaucracy, petty corruption.